CDK4/6 inhibition in breast cancer: current practice and future directions. (16th July 2018) - Pernas, Sonia; Tolaney, Sara M.; Winer, Eric P.; Goel, Shom
The cyclin D/cyclin-dependent kinases 4 and 6 (CDK4/6)–retinoblastoma protein (RB) pathway plays a key role in the proliferation of both normal breast epithelium and breast cancer cells. A strong rationale for inhibiting CDK4/6 in breast cancers has been present for many years. However, potent and selective CDK4/6 inhibitors have only recently become available. These agents prevent phosphorylation of the RB tumor suppressor, thereby invoking cancer cell cycle arrest in G1. CDK4/6 inhibitors have transited rapidly from preclinical studies to the clinical arena, and three have already been approved for the treatment of advanced, estrogen receptor (ER)-positive breast cancer patients on account of striking clinical trial results demonstrating substantial improvements in progression-free survival. ER-positive breast cancers harbor several molecular features that would predict their sensitivity to CDK4/6 inhibitors. As physicians gain experience with using these agents in the clinic, new questions arise: are CDK4/6 inhibitors likely to be useful for patients with other subtypes of breast cancer? Are there other agents that could be effectively combined with CDK4/6 inhibitors, beyond endocrine therapy? Is there a rationale for combining CDK4/6 inhibitors with novel immune-based therapies? In this review, we describe not only the clinical data available to date, but also the biology of the CDK4/6 pathway and discuss answers to these questions. In particular, we highlight that CDK4 and CDK6 govern much more than the cancer cell cycle, and that their optimal use in the clinic depends on a deeper understanding of the less well characterized effects of these enzymes.